Beyond the truth - Holt, Anne, 1958- (Holt, Anne, 1958- Hanne Wilhelmsen novel., 2016)
Investigating the Christmas-season murders of four people in the luxurious home of one of Oslo's wealthiest families, Norwegian Police Chief Inspector Hanne Wilhelmsen risks everything to identify a mysterious victim and his reason for being among the others.